2012
DOI: 10.1111/j.1742-4658.2012.08500.x
|View full text |Cite
|
Sign up to set email alerts
|

The kynurenine pathway and quinolinic acid: pivotal roles in HIV associated neurocognitive disorders

Abstract: This brief review will first consider HIV associated neurocognitive disorder followed by the current understanding of its neuropathogenesis. Against this background the role of the kynurenine pathway will be detailed. Evidence both direct and indirect will be discussed for involvement of the kynurenine pathway at each step in the neuropathogenesis of HIV associated neurocognitive disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 69 publications
(107 reference statements)
1
47
0
Order By: Relevance
“…Katz et al, however, advocated that the role of kynurenine metabolites in immune response and inflammation may not be simple, 31,32 referring to the notion that depletion of tryptophan from T cells and/or tryptophan metabolites themselves might make T cells unable to trigger the appropriate immune reaction. 33 In the present study, kynurenine was associated with CRP, as were some metabolites of the kynurenine pathway in previous studies. 30 Given that inflammation is associated with muscle dysfunction 34, 35 and reduced functional capacity, 36 inflammation may be a common background both for higher kynurenine and impaired functional capacity observed in the present study.…”
Section: Potential Mechanismsmentioning
confidence: 68%
“…Katz et al, however, advocated that the role of kynurenine metabolites in immune response and inflammation may not be simple, 31,32 referring to the notion that depletion of tryptophan from T cells and/or tryptophan metabolites themselves might make T cells unable to trigger the appropriate immune reaction. 33 In the present study, kynurenine was associated with CRP, as were some metabolites of the kynurenine pathway in previous studies. 30 Given that inflammation is associated with muscle dysfunction 34, 35 and reduced functional capacity, 36 inflammation may be a common background both for higher kynurenine and impaired functional capacity observed in the present study.…”
Section: Potential Mechanismsmentioning
confidence: 68%
“…The potential value of the kynurenine pathway for the development of new drugs acting in disorders such as these, in which a degree of neuronal damage is involved, has been discussed previously [90] In addition, the identification of a range of molecular targets such as GPR35, Finally, the parallel work that has developed since the early 1980s of the actions of kynurenines in the CNS and their effects in the immune system seem to be moving closer towards an integrated view of their interaction. That may in turn result in the development of compounds that can regulate changes in the processes of CNS neurotransmission directly, but which can also modify the development and progression of inflammatory reactions that increasingly seem to underlie chronic CNS disorders such as AD and HD, but may also be relevant to conditions such as multiple sclerosis (MS) [91] and infection-induced dementias [92]. This is certainly a pathway that is likely to become more intriguing in the future.…”
Section: Kynurenines and Drug Developmentmentioning
confidence: 99%
“…Despite our findings using these HD models, many studies have shown a strong correlation between IDO (indoleamine 2,3-dioxygenase, a key enzyme responsible for the production of kynurenine from tryptophan) activation, in situ-generated Quin neurotoxic levels, and the extent of neurodegeneration (Kandanearatchi and Brew, 2012;Plangar et al, 2012;Stone and Darlington, 2013;Vamos et al, 2009). The role of kynurenine catabolism in the regulation of the immune response is important, and this is difficult to evaluate in mouse models of HD.…”
Section: Discussionmentioning
confidence: 86%